ANALYSIS AND FASIES DISTRIBUTION OF PRETALANGAKAR FORMATION, CIPUTAT SUB BASIN, NORTH WEST JAVA BASIN - KOESUMADEWI, FUJI
The Ciputat Sub Basin is located on the northwestern part of Java Island. Hydrocarbon exploration has been conducted for over the last 50 years, numerous hydrocarbon exploration and production activities were recorded within the basin until this 2013. The latest hydrocarbon discovery within clastic reservoir of PreTalangakar Formation at Pondok Makmur (PDM)-1 well, located on east side of Rengasdengklok High with stratigraphic concept, has open new opportunity for exploration to obtain bigger discovery with the same concept at the other part of Ciputat Sub Basin. The PreTalangakar Formation at Ciputat Sub Basin is proved perform as a reservoir as well as a source rock that has generated hydrocarbon. Reservoir analysis and distribution of PreTalangakar Formation is become one of interested topic to be analyzed, in order to get bigger enhancement of hydrocarbon resources at North West Java Basin, in general, and particularly at Ciputat Sub Basin. Data of 15 exploration and 6 development well, combined with 3D seismic data were used to analyze and to interpreted fasies and reservoir distribution of PreTalangakar Formation at Ciputat Sub Basin. In this study, tectonostratigraphy approach is used where PreTalangakar Formation is a Syn Rift sequences, resting unconformably on the basement rocks. Based on biostratigraphy data. PreTalangakar Formation is deposited at Littoral to Inner Neritic Environment. Core data with a total length of 13 m from two wells , show lenticular bedding , flaser/flame structure and reverse gradded bedding structural sediment. The FMI data from several wells also show parallel lamination and heterolithic lithology. In general, the present of bioturbated and rootlets are also common seen on mostly of FMI data in Pondok Makmur area. Based on Gamma Ray log pattern , the PreTalangakar Formation can be divided into two zones as follows: lower part with a relative fining upward sequences and upper part with relative coarsening upward sequences. With combination of attribute seismic data, PreTalangakar Formation at Ciputat Sub Basin were interpreted as a Tide-dominated Estuary at the lower zone and Tide-dominated Delta at the upper zone. There are also exploration opportunity to get bigger hydrocarbon resources at the southern part of Pondok Makmur Field.